Crystallographic characterization of three cathinone hydrochlorides new on the NPS market: 1‐(4‐methylphenyl)‐2‐(pyrrolidin‐1‐yl)hexan‐1‐one (4‐MPHP), 4‐methyl‐1‐phenyl‐2‐(pyrrolidin‐1‐yl)pentan‐1‐one (α‐PiHP) and 2‐(methylamino)‐1‐(4‐methylphenyl)pentan‐1‐one (4‐MPD). Issue 1 (29th December 2021) - Rojkiewicz, Marcin; Kuś, Piotr; Książek, Maria; Kusz, Joachim
Abstract : The crystallographic structures and physicochemical characterization are reported for three cathinone (4‐MPHP, α‐PiHP and 4‐MPD) hydrochlorides new to the psychoactive substances (NPS) market. Abstract : Cathinones belong to a group of compounds of great interest in the new psychoactive substances (NPS) market. Constant changes to the chemical structure made by the producers of these compounds require a quick reaction from analytical laboratories in ascertaining their characteristics. In this article, three cathinone derivatives were characterized by X‐ray crystallography. The investigated compounds were confirmed as: 1‐[1‐(4‐methylphenyl)‐1‐oxohexan‐2‐yl]pyrrolidin‐1‐ium chloride (1, C17 H26 NO + ·Cl −, the hydrochloride of 4‐MPHP), 1‐(4‐methyl‐1‐oxo‐1‐phenylpentan‐2‐yl)pyrrolidin‐1‐ium chloride (2 ; C16 H24 NO + ·Cl −, the hydrochloride of α‐PiHP) and methyl[1‐(4‐methylphenyl)‐1‐oxopentan‐2‐yl]azanium chloride (3 ; C13 H20 NO + ·Cl −, the hydrochloride of 4‐MPD). All the salts crystallize in a monoclinic space group: 1 and 2 in P 21 / c, and 3 in P 21 / n . To the best of our knowledge, this study provides the first detailed and comprehensive crystallographic data on salts 1 –3 .